What Happens To your Food? - Alastair Smith (London, United Kingdom Usborne Publishing Ltd, 1999)
What Happens to Your Food? offers an introdu ction to food, eating and digestion, using interactive fold- out flaps to help explain to young readers the whole fascina ting journey of a meal through the human body. '
Keywords: Who We Are -- -Body Systems -- -Healthy Lifestyle